Research on intrusion detection of industrial control system - Ying-xu LAI; Zeng-hui LIU; Xiao-tian CAI; Kai-xiang YANG (Tongxin xuebao)
Industrial control system was an important part of national critical infrastructure,once it was suffered from the cyber attack,it would cause property damage,casualties and other serious disasters.For providing theoretical supports to industrial security researchers,the features of attacks in an industrial control system and the difficulties of detection to these attacks were introduced.Then,a survey of intrusion detection technologies used by the industrial control systems was given.Also,the performance and characteristic were compared for the different types of detection technologies.Fi-nally,an industrial intrusion detection research was generated.